Integrating kierkegaard’s existentialism into Islamic higher education mental health services : a qualitative study in central java - Henie Kurniawati; Kurnia Sari Wiwaha; Shaula Astika Putri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Mental health is crucial in empowering individuals, families, and communities, significantly impacting well-being and productivity. However, mental health is often neglected, especially among adolescents, who show a high prevalence of mental health disorders in Indonesia. This situation has prompted universities, particularly in Central Java, to establish mental health services. This study aims to understand the form of student mental health in Central Java according to Søren Kierkegaard's existentialism. This study analyzed the condition of students and the mental health services provided in the college service unit. To achieve this objective, the researchers employed a qualitative research method processed with N-Vivo version 14. They used integration theory between philosophy (Søren Kierkegaard's existentialism) and psychology (resilience, hope, self-efficacy, quality of life, and social support). The mental health of students is still in various stages, starting from the pre-college period to the lecture period, and the majority are still at the ethical level. This finding is supported by the lack of integration of professions in mental health service units that provide services to guide students to reach the religious level